Cardiac Troponin Levels in Neonates Who Require ECMO for Noncardiac Indications Are Elevated in Nonsurvivors - Astoria, Mark T.; Karam, Simon E.; Moores, Russell R., Jr.; Rozycki, Henry J. (American Journal of Perinatology, 2015)
Objective The aim of the study is to determine the utility of cardiac troponin (cTnI) as a marker of mortality and morbidity in newborn infants who require extracorporeal membrane oxygenation (ECMO).Study Design Retrospective medical chart analysis of term or near-term newborn infants treated with ECMO from 2002 to 2012 at a single Level III neonatal intensive care unit. Data analyzed included serial serum cTnI measurements, clinical and demographic characteristics, pre-ECMO laboratory values, and ECMO laboratory values and outcomes.Results Survival (27/46) was significantly related to birth weight (3,413.9 ± 662.3 vs. 2,667.7 ± 478.3 g, p < 0.001), outborn status (22/30 vs. 5/13, p = 0.0021), and the absence of a congenital diaphragmatic hernia (22/30 vs. 5/18, p = 0.0021). Mean peak cTnI did not differ between survivors and nonsurvivors but when peak cTnI was < 2.8 ng/mL, survival was 64% compared with 22% when it was > 2.8 ng/mL (p = 0.0224; odds ratio = 0.160, 95% confidence interval = 0.0292–0.8778). By multivariate analysis, peak cTnI > 2.1 was a significant risk factor for nonsurvival, p = 0.0497. The area under the curve of a receiver-operator analysis using peak cTnI > 2.1, birth weight, and birthplace was 0.89, p < 0.001.Conclusion cTnI is an independent biomarker for poor outcome in neonates who receive ECMO therapy for noncardiac generations.
Keywords: biomarker; congenital anomalies; cardiac ischemia; extracorporeal membrane oxygenation